Victims, Perpetrators and Bystanders: Atrocity and Its Aftermath in the Films of Jasmila Žbanić - Aydın Aitchison, Andy (The British journal of criminology, 2024)
The paper excavates ‘implicit criminologies’ concerning victims, perpetrators and bystanders from four films by Bosnian director Jasmila Žbanić: Grbavica (2006); On the path (2010); For those who can tell no tales (2013) and Quo Vadis, Aida? (2020). I argue that in criminological terms, Žbanić’s work is strongest, and has greatest transformative potential, as an example of cinematic victimology. This is produced through characters who simultaneously encapsulate particular (ethnicized) and universal elements in micro-level stories of the individual in a larger social, political and historical context. Focussing on this form of universalism, I question an ethical standard of inclusivity in atrocity cinema which calls for a single film or director to directly represent victims of all ethnic groups.